Retailer's characteristics and compliance with the single-use plastic bag ban - Bishal Bharadwaj; Mukti Nath Subedi; Rajesh Kumar Rai (Sustainability Analytics and Modeling, 2023)
The increasing use of single-use plastic bags has led to a global concern. Cities in developing countries are enforcing a (single-use) plastic bags ban to reduce the use of plastic in the retail supply chain. In Nepal, some retailers such as fashion outlets and pharmacies support the ban and others like dairy shops protest. This analysis aims to investigate how retailer heterogeneity in terms of shop characteristics and social association influences bag use behavior and compliance with the plastic bag ban in Nepal. This study based on the 1300 retailers’ plastic bag use data in three different plastic bag ban scenarios from 13 municipalities of Nepal shows that retailers’ response to the ban depends on their shop type, the nature of the goods they sell, and their social association. In addition, retailers' perception also affect their response to the plastic ban decision. Their perception of the performance of regulatory authority is likely to affect their compliance. Similarly, retailers who consider that the municipality has strong enforcement in place, tend to cooperate with the ban. This article highlights the need for retailer-specific interventions to reduce bag use.